2015
DOI: 10.1177/2167479515588761
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Dude Time!”

Abstract: The last quarter century has seen a dramatic movement of girls and women into sport, but this social change is reflected unevenly in sports media. This study, a 5-year update to a 25-year longitudinal study, indicates that the quantity of coverage of women’s sports in televised sports news and highlights shows remains dismally low. Even more so than in past iterations of this study, the lion’s share of coverage is given to the “big three” of men’s pro and college football, basketball, and baseball. The study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(37 citation statements)
references
References 43 publications
4
31
0
2
Order By: Relevance
“…Various studies have confirmed this fact and acknowledged the positive impact of targeted advertising on the tendency of people toward recreational sports (30,31). Besides, the small share of women's sports in television broadcasting over time, despite an increase in their participation, has been emphasized by Cooky (2015) and Waaneberg (2011) (32,33). In his study, Cooky (2015) he investigated the coverage of women's sports in television' sports news in three local news agencies in Los Angeles for 6 weeks and concluded that the level and quality of women's sports coverage were at the lowest level and that women's sports news were overshadowed and marginalized by men's (32).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Various studies have confirmed this fact and acknowledged the positive impact of targeted advertising on the tendency of people toward recreational sports (30,31). Besides, the small share of women's sports in television broadcasting over time, despite an increase in their participation, has been emphasized by Cooky (2015) and Waaneberg (2011) (32,33). In his study, Cooky (2015) he investigated the coverage of women's sports in television' sports news in three local news agencies in Los Angeles for 6 weeks and concluded that the level and quality of women's sports coverage were at the lowest level and that women's sports news were overshadowed and marginalized by men's (32).…”
Section: Discussionmentioning
confidence: 96%
“…Besides, the small share of women's sports in television broadcasting over time, despite an increase in their participation, has been emphasized by Cooky (2015) and Waaneberg (2011) (32,33). In his study, Cooky (2015) he investigated the coverage of women's sports in television' sports news in three local news agencies in Los Angeles for 6 weeks and concluded that the level and quality of women's sports coverage were at the lowest level and that women's sports news were overshadowed and marginalized by men's (32). In addition, women's sports in the foreign media, for the most part, are aimed at presenting women as goods and for the purpose of showing a healthy body, while, in case of men, only performance is focused (34).…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently found that the volume of women's sports media coverage is less than men's sports (Bernstein, 2002;Cooky, Messner, & Musto, 2015;Fink, newsworthiness, then, should be viewed as originating in the structural, social, and cultural underpinnings of the profession.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The academic discourse on women's sport in the Global North has centered on an observation that, despite advances in women's participation rates, it remains a profoundly gendered institution where men are considered naturally more skilled and competent (Cooky, Messner, & Musto, 2015;Messner, 2009;Wachs, 2005). For example, Messner (2009) argued that young sportwomen are often positioned as less knowledgeable and have limited access to information that could help them develop competence and autonomy in their practice.…”
Section: Gender and Sportmentioning
confidence: 99%